Mycoplasmas and Mycoplasmosis - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
The paper underlines the importance of Mycoplasmas on the course of pneumonia mostly in children. Mycoplasmas constitute a distinct class from bacteria since they lack a cell wall. There is a list of the main mycoplasmas pathogenic to humans with a special attention to Mycoplasma pneumoniae. The use of Polymerase Chain Reaction (PCR) is fundamental for serological diagnosis. The clinical history is mostly favorable to prompt recovery. Then are problems concerning long-term antibiotic treatments. Very important studies are reported on the hypothesis that the mycoplasmas could at as co-factors for the progression of HIV infection and represent one of the main weapons of potential bacteriological wars. Transferred genome can create life in a new microbe and opens broader horizons for scientific research.